TEACHING NARRATIVE TEXTS THROUGH JOURNAL : A Case Study at One of International Secondary Schools in Bandung - Yohan, - (2009)
This is a report of a case study designed to examine Teaching Narrative Texts through Journal at one of International Secondary Schools in Bandung in academic year 2008/2009. Using descriptive method, this case study aimed at describing the kinds of activity that take place in teaching Narrative Texts through journal, knowing the students' opinions about writing Narrative Texts through journal, exploring the obstacles that the students encountered in writing Narrative Texts through journal, and identifying the benefits that they might obtain from writing Narrative Texts through journal. There were six students and one EFL writing teacher as the participants involved. The data concerning the kinds of activity that take place in teaching Narrative Texts through journal was collected through observation. The data concerning the students' opinions, their obstacles, and the benefits that they obtained from writing Narrative Texts through journal were collected through questionnaire and interview. Meanwhile, the students' written works (journal) were used to evidence the benefits that they obtain from writing Narrative Texts through journal, including writing skills development and vocabulary development. In this study, the teacher's interview was also used to confirm the data from students. The collected data were then transcribed, interpreted, and analyzed. The results show that there are three general kinds of activities took place in the process of teaching and learning Narrative Texts through journal. They are journal writing (building knowledge of the field, starting out and keeping going), Narrative Texts instruction (building knowledge of the field, modeling, and independence construction), and grammar instruction. Journal writing was applied as teaching technique to increase students' writing habits, Narrative Texts instruction was applied which based on Genre-Based as teaching approach to reach maximal results of teaching Narrative Texts and to help students develop their insights and skills about text types, and grammar instruction was applied to increase students' understanding about the linguistic structure of Narrative Texts. Then, the positive and negative opinions relating to writing Narrative Texts through journal were given by the respondents. The data also indicate that in writing Narrative Texts through journal, the respondents encountered a lot of obstacles, they are: 1) procedural problems, which were likely to be the major problems encountered by the students; 2) Academic problems; and 3) Non-academic problems. However, whatever the problems that the students dealt with, each of them obtained a lot of benefits from writing Narrative Texts through journal, one of them is their writing skills might be better as can be seen from their written works (journal).